Malnutrition and body composition in urban and rural schoolchildren: a cross-sectional study in San Rafael, Mendoza (Argentina). - Garraza, Mariela (2016)
Objectives: The aim of the present study was to analyze the nutritional status and body composition of children from San Rafael, Mendoza, avoiding urban and rural categorization by generating subpopulations as a function of their socio-environmental characteristics. Methods: A cross-sectional study was performed in 3,596 schoolchildren from 4.0 to 13.9 years of age. Body weight, height, upper arm circumference, and triceps skinfold were measured. Body mass index, total muscle, and fat areas of the arm were calculated. To estimate nutritional status and body composition, the NHANES III reference was used. The socio-environmental variables were surveyed using a structured questionnaire. These variables were processed by categorical principal-component analysis (catPCA). Results: The catPCA allowed the differentiation of four groups, three with urban characteristics (high urban, medium urban, impoverished urban), and a rural group. Stunting occurred at a higher rate in the impoverished urban group, and the occurrence of underweight children was higher in the rural group. The prevalence of excess weight varied in the range of 20–26%. The latter value corresponded to children of the high urban group, who also did not show reduced muscle mass. Conclusion: Children from San Rafael presented differences in nutritional condition and body composition associated with pronounced socio-environmental heterogeneity. Thus, we could observe a gradient from the “high urban” group, with better social, economic, and sanitation conditions and at the same time a more obesogenic environment to the “impoverished urban” and “rural” groups, whose vulnerability reflected a higher prevalence of child undernutrition and the association with excess weight and reduced muscle mass.